Implementação da metodologia lean em uma instituição de ensino superior pública: revisão de literatura e estudo de caso. - Almeida Junior, Antonio Tadeu de (Universidade Federal de São Carlos, 2026)
This dissertation investigates the application of the Lean methodology in several Higher Education Institutions (HEIs), combining a systematic literature review with a proposal for practical implementation in the diploma issuance process at a public university. Given the growing interest in the application of Lean and Lean Six Sigma (LSS) in service environments, including the educational sector, this work aims to identify processes that benefit from its application, the tools used, the barriers faced, and strategies for overcoming them. The first stage consisted of a Systematic Literature Review (SLR), conducted in the Scopus and Web of Science databases, resulting in the analysis of 88 articles, of which 48 empirical studies were selected to answer the research questions. The analysis allowed for mapping the areas of application, the types of projects developed, the most frequently used tools, and the adjustments made for the context of HEIs. The second stage proposes the application of Lean in the undergraduate diploma issuance process, using a case study in a public HEI, seeking to evaluate gains in efficiency, response time, and waste reduction. This research contributes to the consolidation of knowledge about Lean in higher education, especially in the public sector, and provides support for managers interested in improving academic and administrative processes in HEIs.
Implementation of the Lean methodology in a public higher education institution: literature review and case study.
Keywords: Diploma Universitário; Lean; Serviço Público; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA; 9. Indústria, Inovação e Infraestrutura